Benefits of short-term dietary restriction in mammals - Robertson, Lauren T. (2013)
Dietary or calorie restriction (DR, CR), defined as reduced food intake without malnutrition, imparts many benefits in model organisms. Extended longevity is the most popularized benefit but the least clinically relevant due to the requirement for long-term food restriction. DR also promotes stress resistance and metabolic fitness. Emerging data in experimental models and in humans indicate that these benefits occur rapidly upon initiation of DR, suggesting potential clinical relevance. Here we review data on the ability of short-term DR to induce beneficial effects on clinically relevant endpoints including surgical stress, inflammation, chemotherapy and insulin resistance. The encouraging results obtained in these preclinical and clinical studies, and the general lack of mechanistic understanding, both strongly suggest the need for further research in this emerging area.